Effect of applying finishing products and sanding on the surface of marupa wood - Hermida de Paula, Marcella; Rossi Silva de Mesquita, Robert; de Almeida Costa, Mírian; Carlos Gonçalez, Joaquim; A. Ananías, Rubén; Janin, Gèrard (Maderas. Ciencia y Tecnología, 2020)
The effect of applying cetol and varnish finishing products and sanding on the surface roughness and colour of marupa (Simarouba amara) wood was evaluated. Three coats of each product were applied and two sandpaper grits were used, 280 and 320). The analyzes were performed on untreated samples and between each coat of products in order to analyze the effect of sanding, the products and the number of coats. According to colorimetry, the L* value for the control treatment was 82.83 and the treatments reduced the L* to 61.70 on average for the cetol treatment and 77.09 for the varnish treatment, showing that the cetol darkened the wood more than the varnish. The yellowish and reddish pigmentations became more intense according to the positive values of Δa* and Δb*, especially after applying the cetol. The total colour variation ΔE average was 40.79 for the cetol treatment and 9.83 for the varnish treatment, confirming a much more significant colour change in the cetol treatment. Sanding with different grits did not significantly alter the surface colour. The product application made the wood surface smoother, and was noticeable from the second coat. Sanding reduced roughness on the wood surface, but the finishing product was the largest source of variation.